A dynamic opportunistic preventive maintenance policy for multi-unit series systems with intermediate buffers. (2nd September 2010) - Zhou, Xiaojun; Lu, Zhiqiang; Xi, Lifeng
Commonly, for a multi-unit series system, whenever one of the units stops to perform a preventive maintenance action, preventive maintenance opportunities arise for the other units because combining the preventive maintenance activities can save the system-dependent cost (i.e. downtime cost). This article proposes an opportunistic preventive maintenance policy for multi-unit series systems based on dynamic programming, with integrating the online information of the intermediate buffers. Whenever one of the units reaches its reliability threshold, a preventive maintenance action has to be performed on that unit. An optimal preventive maintenance practice is determined by maximising the short-term cumulative opportunistic maintenance cost savings for the whole system which is a combination of the maintenance cost saving, the downtime cost saving, the penalty cost for advancing the preventive maintenance action and the penalty cost for work in process. Finally, a numerical example is given throughout to show how this approach works.